The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.3346/jkms.2015.30.3.336
|View full text |Cite
|
Sign up to set email alerts
|

Effective Transport for Trauma Patients under Current Circumstances in Korea: A Single Institution Analysis of Treatment Outcomes for Trauma Patients Transported via the Domestic 119 Service

Abstract: In Korea, which still lacks a well-established trauma care system, the inability to transport patients to adequate treatment sites in a timely manner is a cause of low trauma patient survival. As such, this study was conducted to serve as a basis for the establishment of a future trauma transport system. We performed a comparative analysis of the transport time, and treatment outcomes between trauma victims transported by ground ambulance (GAMB) and those transported via the helicopter emergency medical servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
1
13
2
Order By: Relevance
“…In the present study, the median transport time by GEMS was 65 minutes, exceeding the so-called golden hour, which is the time from the accident to the definitive treatment. Although Kim et al ( 35 ) reported that the mean transport time by GEMS was 57 minutes, they did not report any information on patient transfer distance contrary to our study, and whether the study population was comparable with the population transported via H-HEMS was unclear. Diaz et al ( 36 ) showed that helicopter transport was faster than ground transport when requested by scene personnel for a patient who was 45 miles from the trauma center, making patients in this distance range the most likely to benefit from more rapid transport to definitive care centers by helicopter.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In the present study, the median transport time by GEMS was 65 minutes, exceeding the so-called golden hour, which is the time from the accident to the definitive treatment. Although Kim et al ( 35 ) reported that the mean transport time by GEMS was 57 minutes, they did not report any information on patient transfer distance contrary to our study, and whether the study population was comparable with the population transported via H-HEMS was unclear. Diaz et al ( 36 ) showed that helicopter transport was faster than ground transport when requested by scene personnel for a patient who was 45 miles from the trauma center, making patients in this distance range the most likely to benefit from more rapid transport to definitive care centers by helicopter.…”
Section: Discussioncontrasting
confidence: 78%
“…Kim et al ( 35 ) reported the advantage of helicopter transportation based on the fire department system over ground transportation. However, the median helicopter transport time in that study was 60 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…These results support several studies that reported that surviving a major injury was strongly associated with reaching definitive care (that is, a hospital that could provide optimal treatment) as quickly as possible. 16,23,24 However, in this study, the number of emergency medicine specialists and total specialists per ED did not have a significant relationship with the mortality rate, unlike the results of previous studies. 12,13,25 Regional emergency medical resources and mortality…”
Section: Discussioncontrasting
confidence: 57%
“…As a result, only two regional trauma centres have opened nationwide as of July 2014. 24 Therefore, the government's policy to double the number of regional emergency medical centres and improve the criteria of facilities, equipment, and personnel seems to have been only partially effective. A more effective way to improve the emergency medical system may be to not only increase the quantity of emergency medical resources, but also focus on increasing their quality.…”
Section: Cjem Jcmumentioning
confidence: 99%
See 1 more Smart Citation